“The workload is staggering”: Changing working conditions of stay-at-home mothers under COVID-19 lockdowns - Aslam, Awish; Adams, Tracey L. (Gender, Work and Organization, 2022)
The COVID-19 pandemic has drawn attention to the home as a work environment, but the focus has centered on the experiences of paid workers. Stay-at-home mothers (SAHMs), for whom the home was already a workplace, have received little attention. This article explores how pandemic-induced lockdowns impacted SAHMs' working conditions and their experiences of childrearing. Combining a Marxist-feminist conceptualization of domestic labor with a labor process framework, we performed a qualitative content analysis of vignettes SAHMs shared about their day-to-day domestic labor in an online mothering community. Our findings show that, under lockdown conditions, the primacy given to partners' paid work combined with children's increased demands for care and attention reduced SAHMs work autonomy and exacerbated gender inequalities in the home. Combining labor process theory with literature on motherwork illuminates the home as a gendered work environment and enhances understanding of how changing conditions of domestic labor can intensify gender inequalities (and workers' awareness of them) that typically remain “hidden in the household.”. © 2022 John Wiley & Sons Ltd.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; care; discipline; féminisme marxiste; féminisme matérialiste; inégalités; maternité; mères au foyer; projet charge mentale; périodes historiques; ressource en ligne; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail de reproduction

Réenchanter le monde: féminisme et politique des communs - Federici, Silvia; Linebaugh, Peter; Grunenwald, Noémie (Entremonde, 2022)
« Silvia Federici présente une critique de la politique des communs dans une perspective féministe. De son vécu au Nigeria et de ses rencontres avec des militantes d'Amérique latine et du monde entier, Federici révèle les luttes quotidiennes des femmes contre la spoliation de leur terre, de leur logement et nourriture. De ses recherches historiques, elle compare les enclosures, qui ont permis la naissance du capitalisme par la destruction des communs et la prolétarisation des populations rurales, aux « nouvelles enclosures » au cœur de la phase actuelle d'accumulation capitaliste mondiale. Cet ouvrage soutient que les luttes autour de la reproduction sociale sont cruciales autant pour notre survie économique que pour la construction d'un monde libéré des hiérarchies et des divisions que le capital a implantées dans le corps du prolétariat international. Federici considère que les communs ne doivent pas être compris comme des îlots de partage dans un océans de relations d'exploitation, mais plutôt comme des espaces autonomes à partir desquels défier l'organisation capitaliste de la vie et du travail. »– Quatrième de couverture.
Section: 303 pages ; 21 cm.
Keywords: approches et analyses; com5170; communs; cours; discipline; droits des femmes*; féminisme matérialiste; histoire et politique; justice sociale; philosophie; philosophie politique; premier cycle; sciences humaines; thématiques